Bio-efficacy of denatonium benzoate added formulation of bromadiolone against commensal rodents. (February 2016) - Tripathi, R.S.; Chaudhary, Vipin
Abstract: Present day rodent management technology mostly relies on use of rodenticides, which is unsafe for human beings and other non-targets. Denatonium benzoate (DB) is an intensely bitter and non-toxic substance which is detectable by humans at a concentration of 10 ppb. Denatonium benzoate added wax block formulation of bromadiolone (0.005%) (an anticoagulant rodenticide) was evaluated against commensal rodents (house rat, Rattus rattus and lesser bandicoot rat, Bandicota bengalensis ), which are always found in the proximity of pets, domestic animals and human beings. Single day exposure to bromadiolone (0.005%) formulation with DB and without DB in no-choice tests yielded 100% mortality in both the test rodent species in 2–11 days. The amount of poison bait ingested by R. rattus and B. bengalensis for both the formulations did not differ significantly, ranging between 5.87 - 7.30 and 6.51–6.71 g/100 g body weight, respectively. In choice tests in the presence of alternate plain food (broken wheat grain), consumption of both the formulations of bromadiolone (0.005%) (with and without DB) was similar to plain food at both the exposure periods (1 and 2 days), indicating a good acceptability of test rodenticide. However, mortality with a single day exposure to bromadiolone (0.005%) formulation with DB was 70% and without DB was 60–80% in both test rodent species within 3–14 days. With a two days exposure period, mortality was 100% in both the species of test rodents in 3–13 days. Single day choice test between the formulations revealed that intake of baits of both formulations by both the test rodents was similar i.e., in the range of 8.16–8.94 g/100 g b wt (bromadiolone with DB) and 8.20–9.5 g/100 g b wt (bromadiolone without DB) indicating that incorporation of a bittering agent (DB) with bromadiolone did not alter the consumption of poison in both the test species. In field trials the mean control success as assessed by census baiting and trapping methods with the application of bromadiolone (0.005%) with DB ranged between 54.0% (houses and shops) to 68.4% (poultry farms) and was 55.6% (houses and shops) to 68.4% (poultry farms) in treatments with bromadiolone (0.005%) without DB. It can be concluded that denatonium benzoate could be a best additive in rodenticidal formulations as the acceptability, palatability and toxicity in the laboratory and also its performance in field in managing the pest rodents were not altered. Highlights: Rodent management mostly relies on use of rodenticides. Rodent management mostly relies on use of rodenticides. Bitrex, denatonium benzoate (DB) added formulation of bromodiolone (0.005%) was evaluated. It was evaluated against two commensal rodents under laboratory and field conditions. Its toxicity and acceptability was comparable with its commercial formulation.